Pitch, Paint, Varnish and the Changing Colour Schemes of Royal Navy Warships, 1775–1815: A summary of existing knowledge. Issue 1 (2nd January 2020) - Vale, Brian
Abstract : It is a long-standing assumption that the colour scheme of British warships between 1775 and 1815 changed from yellow hulls, through the yellow and black Nelson chequer to the ubiquitous black and white; while the interiors and bulwarks were first painted red, then yellow ochre, then a range of light colours including green. In the light of recent debate on the authentic Trafalgar livery of HMS Victory, the object of this article is to summarize existing knowledge on the subject, to extend it using documentary evidence and to arrive at an accurate picture of the evolving styles of decoration of the Royal Navy from the colourful ornamentation of the eighteenth century to the austere black and white of the post-Georgian period.